Antispasmodic activity of apigenin and luteolin, two components of Dracocephalum kotschyi extract, on rat ileum contractions - Hassan Sadraei; Mostafa Ghanadian; Golamreza Asghari; Nastaran Sekhavati (Shahrekord University of Medical Sciences, 2018)
Introduction: Aerial parts of Dracocephalum kotschyi have been used as antispasmodic agents in Iranian traditional medicine. Recent pharmacological studies confirmed antispasmodic activity of D. kotschyi extract. The objective of this research was to investigate antispasmodic activities of apigenin and luteolin to find out if they are responsible for the spasmolytic activity of hydroalcoholic extract of D. kotschyi. Methods: Aerial parts of D. kotschyi were extracted with ethanol. Antispasmodic effect of hydroalcoholic extract of D. kotschyi, apigenin and luteolin were examined on KCl and/or acetylcholine (ACh)-induced contractions in rat isolated ileum. Results: Hydroalcoholic extract of D. kotschyi concentrations-dependently inhibited KCl and ACh induced contractions with IC50 values of 41 ± 10 μg/mL and 133 ± 19 μg/mL, respectively. Apigenin concentrations-dependently inhibited KCl and ACh induced contractions with IC50 values of 57 ± 12 μM and 80 ± 18 μM, respectively. Luteolin concentrations-dependently inhibited KCl induced contractions with IC50 values of 68 ± 14 μM. Loperamide reduced both KCl and ACh induced contraction with IC50 values of 189 ± 44 nM and 82 ± 20 μM, respectively. Conclusion: In this study apigenin and luteolin were identified as two active ingredients responsible for antispasmodic activities of D. kotschyi extract.